Pre-treatment of daily teriparatide enhances the increase of bone mineral density in cortical bones by denosumab therapy - Kamimura M; Taguchi A; Nakamura Y; Koiwai H; Ikegami S; Uchiyama S; Kato H (Dove Medical Press, 2018)
Mikio Kamimura,1 Akira Taguchi,2 Yukio Nakamura,3,4 Hidefumi Koiwai,5 Shota Ikegami,3 Shigeharu Uchiyama,3 Hiroyuki Kato3 1Center for Osteoporosis and Spinal Disorders, Kamimura Orthopedic Clinic, Matsumoto, Japan; 2Department of Oral and Maxillofacial Radiology, Matsumoto Dental University, Shiojiri, Japan; 3Department of Orthopaedic Surgery, Shinshu University School of Medicine, Matsumoto, Japan; 4Department of Orthopedic Surgery, Showa-Inan General Hospital, Komagane, Japan; 5Koiwai Orthopedic Clinic, Komoro, Japan Background: While it is well known that teriparatide (TPTD) increases bone mineral density (BMD) in osteoporotic patients, it is unknown whether TPTD pretreatment affects BMD after denosumab (DMAb) therapy.Methods: Fifty-seven patients in TPTD-pretreated group and 35 patients in DMAb-alone group had been further analyzed, all of whom were treated by DMAb for 1.5 years. Vitamin D (400 IU) and Ca (600 mg) supplementation was used in all patients. The BMD of lumbar 1–4 vertebrae (L-BMD), bilateral total hips (H-BMD), and bilateral femoral neck (FN-BMD) was quantified at first visit, and at 4, 8, 12, and 18 months after daily TPTD treatment following four times DMAb treatment.Results: There were significant differences in L-BMD (p=0.004) and H-BMD (p=0.026) at baseline between TPTD-pretreated and DMAb-alone groups, although there was no significant difference in FN-BMD between the two groups. The increase of L-BMD by DMAb therapy was less in TPTD-pretreated group than in DMAb-alone group. There was no significant difference in H-BMD, although percent changes of H-BMD tended to be higher in the TPTD-pretreated group than those in the DMAb-alone group. Percent change in FN-BMD at 4 months (p=0.067) and 12 months (p=0.057) tended to be higher in TPTD-pretreated group than in DMAb-alone group. Percent change in FN-BMD at 18 months was significantly higher in TPTD-pretreated group (p=0.004) than in DMAb-alone group.Conclusion: These findings suggest that the pretreatment of TPTD might have enhanced the increase of BMD in cortical bones treated by DMAb. Thus, it is favorable that TPTD can be used for osteoporotic patients who have high fracture risks with cortical bones. Keywords: bone mineral density, cancelleous bones, cortical bone, daily teriparatide, denosumab, osteoporosis